Rancang Bangun dan Implementasi Sistem Lonceng Gereja Berbasis Digital di Gereja GPI Papua Jemaat Kristus Mopah Lama - Richard Semuel Waremra; Daniel Parenden (Yayasan Literasi Sains Indonesia, 2026)
This community service project designed and implemented a digital church-bell system at GPI Papua Jemaat Kristus Mopah Lama (Merauke, South Papua, Indonesia). The partner previously relied on fully manual bell operation, which often caused delays when the responsible operator was unavailable. The proposed solution integrates an Arduino Mega 2560 controller, a 4×4 matrix keypad for command input, a 16×2 I2C LCD for menu/status display, and a DFPlayer Mini module to play pre-recorded bell and announcement tones stored on a microSD card. The audio output is fed to a PA amplifier and broadcast through a horn speaker installed on the church tower. Implementation stages included needs assessment, hardware–software development, panel assembly, on-site installation, functional testing, and operator training accompanied by an operating and maintenance SOP. Black-box tests confirmed that each keypad command reliably triggered the intended sound sequence, while reset and basic electrical protections functioned properly. The system reduces dependency on a single operator, improves the timeliness of worship calls, and is replicable using affordable off‑the‑shelf components.